Surgıcal + Orthognathıc Treatment Of Impacted Canınes - Onur Şengün; Deniz Sağdıç; Erol Bal; Hüseyin Ölmez; Yavuz S. Aydıntuğ; Ünsal Ünal (Galenos Yayinevi, 1992)
In this study the patients who applied for the GATA Oral Surgery Department owing to having impacted canines in 1986-1990 were told the combination of surgical and orthodontic treatment and advantages and disadvantages of different methods were discussed.